Mental health services for deaf people : treatment advances, opportunities, and challenges - Raaij, Ines Sleeboom-van; Estrada Aranda, Benito Daniel (Gallaudet University Press, 2015)
The World Congress on Mental Health and Deafness first met at Gallaudet University in October 1998, and it has convened five more times in the succeeding years. This volume collects the very best research presented at the Fifth World Congress, which took place in Monterrey, Mexico, in 2012. The eighteen international contributors represent the pioneers of mental health and deafness services in their respective countries. Volume editors Benito Estrada Aranda and Ines Sleeboom-van Raaij have divided the book into three parts?Mental Health Issues and Treatment, Deaf Populations, and Deaf Children and Their Families. In the first part, the contributors provide in-depth analysis of specific challenges and treatment modalities ranging from the provision of mental healthcare as a basic human right to psychopharmacological treatment, the challenges in developing mental health services for deaf and hard of hearing people in countries where none exist, and new treatment therapies. Part two looks at issues of self-esteem and cultural identity among deaf and hard of hearing adults in Greece and Cyprus, the services for deaf people at a public health clinic in Austria, and the quality of life among Latino Deaf bilinguals in the United States. In the last part, the contributors focus on mental health issues found in deaf children and adolescents and on the relationships between deaf teenagers and their hearing mothers. The volume concludes with a case study of a prelingually deaf child diagnosed as autistic. Taken all together, these cutting-edge articles explore the important issues within the specialized area of mental health and deafness.